Turnover Intention Among Employees In Pakistani Banks: Examining The Role Of Ethical Climate And Organizational Commitment - Yasin, Raheel (2020)
In the effort to contribute a solution to this problem. this study investigates the impact of compensation, job stress, workplace discrimination and career growth towards the organizational commitment in the banking sector of Pakistan. Furthermore, this study investigated the moderating effect of ethical climate in the relationships between compensation, job stress, workplace discrimination, and career growth towards organizational commitment. This study likewise evaluated the mediating effect of organizational commitment between the relationships of compensation, job stress, workplace discrimination, career growth towards turnover intention